Path dependencies versus efficiencies in regulation: Evidence from "old" and "new" broadband markets in the EU. (September 2019) - Briglauer, Wolfgang; Camarda, Enrico Maria; Vogelsang, Ingo
Abstract: This paper examines the determinants of sector-specific regulation imposed on broadband markets related both to efficiency objectives of regulators and to those of narrowly defined interest groups. We test hypotheses derived from the normative and positive theoretical literature employing recent panel data on 27 European Union member states taking into account endogeneity of the underlying regulation and market structure variables. Our empirical specification employs three different estimators based on instrumental variables in order to identify causal effects. We find evidence supporting both regulators pursuing normative objectives and inefficiencies related to regulatory path dependence, bureaucracy goals and an inadequate consideration of competition from mobile broadband networks. Our results call for adjustments in the institutional design of the decision-making process under the current European Union regulatory framework. Highlights: This paper examines the determinants of NGN regulation. We employ recent panel data on 27 European Union member states. We find evidence supporting regulators pursuing normative objectives. We also find evidence suggesting inefficiencies related to path dependence, bureaucracy. Our results call for adjustments in the institutional design of the EU regulatory framework.